Electrical mechanisms of bi-stable memory devices based on an Al/PVK:ZnO NPs/ITO structure with different ZnO NPs annealing temperatures - Onlaor, Korakot; Chaithanatkun, Natpasit; Tunhoo, Benchapol (My University, 2016)
We reported on the influence of the structural properties of zinc oxide nanoparticles (ZnO NPs) on electrical bi-stable device based on an aluminum/poly(9-vinylcarbazole):ZnO NPs/indium-tin oxide structure. ZnO NPs were synthesized by simple precipitation method with different annealing temperatures. When annealing temperature was increased, the ZnO NPs crystallite increased and the ZnO NPs gradually changed shape from nanostar-like to nanospherical. The structural parameters, such as the crystallite size of ZnO NPs and dislocation density, can be calculated from the XRD spectra. The effect of ZnO NPs annealing temperature on memory properties can be measured by current-voltage characteristics and retention time measurements. The maximum ON/OFF current ratio for the memory devices was about 103 and the devices exhibited the Write-Once, Read-Many (WORM) memory type. The operating mechanisms of the memory device were analyzed using theoretical models, in which electrons trapping in the ZnO NPs and electrons tunneling among a PVK matrix by direct tunneling process were discussed.
Keywords: Memory; Nanoparticles; Precipitation; PVK; ZnO